KARAKTERISTIK MUTU KIMIA MADU HUTAN LEBAH Apis dorsata DI KECAMATAN LUNYUK - Pathiassana, Mega Trishuta (Jurnal Ilmu Pangan dan Hasil Pertanian, 2022)
Apis dorsata forest honey is one of the superior products of communities bordering forest areas such as people in Lunyuk District. One of the important things to know the quality of forest honey is chemical quality testing. This study aims to analyze the chemical quality characteristics of forest honey originating from Lunyuk District in terms of pH value, sugar content, water content, and ash content. The method used in this study is a laboratory test. The test of each parameter was repeated 3 times to ensure the stability and average of each test of these parameters. The results of this study showed a pH value of 3.44; total sugar content 68obrix; water content 32%; and 0.4% ash content.